Using Evidence-Centered Design to Support the Development of Culturally and Linguistically Sensitive Collaborative Problem-Solving Assessments - Oliveri, María Elena; Lawless, René; Mislevy, Robert J. (International journal of testing, 2019)
Collaborative problem solving (CPS) ranks among the top five most critical skills necessary for college graduates to meet workforce demands (Hart Research Associates, 2015 ). It is also deemed a critical skill for educational success (Beaver, 2013 ). It thus deserves more prominence in the suite of courses and subjects assessed in K-16. Such inclusion, however, presents the need for improvements in the conceptualization, design, and analysis of CPS, which challenges us to think differently about assessing the skills than the current focus given to assessing individuals' substantive knowledge. In this article, we discuss an Evidence-Centered Design approach to assess CPS in a culturally and linguistically diverse educational environment. We demonstrate ways to consider a sociocognitive perspective to conceptualize and model possible linguistic and/or cultural differences between populations along key stages of assessment development including assessment conceptualization and design to help reduce possible construct-irrelevant differences when assessing complex constructs with diverse populations.